Evaluation of a cost effective in-house method for HIV-1 drug resistance genotyping using plasma samples. - Devidas N Chaturbhuj (PLoS ONE, 2014)
OBJECTIVES: Validation of a cost effective in-house method for HIV-1 drug resistance genotyping using plasma samples. DESIGN: The validation includes the establishment of analytical performance characteristics such as accuracy, reproducibility, precision and sensitivity. METHODS: The accuracy was assessed by comparing 26 paired Virological Quality Assessment (VQA) proficiency testing panel sequences generated by in-house and ViroSeq Genotyping System 2.0 (Celera Diagnostics, US) as a gold standard. The reproducibility and precision were carried out on five samples with five replicates representing multiple HIV-1 subtypes (A, B, C) and resistance patterns. The amplification sensitivity was evaluated on HIV-1 positive plasma samples (n = 88) with known viral loads ranges from 1000-1.8 million RNA copies/ml. RESULTS: Comparison of the nucleotide sequences generated by ViroSeq and in-house method showed 99.41±0.46 and 99.68±0.35% mean nucleotide and amino acid identity respectively. Out of 135 Stanford HIVdb listed HIV-1 drug resistance mutations, partial discordance was observed at 15 positions and complete discordance was absent. The reproducibility and precision study showed high nucleotide sequence identities i.e. 99.88±0.10 and 99.82±0.20 respectively. The in-house method showed 100% analytical sensitivity on the samples with HIV-1 viral load >1000 RNA copies/ml. The cost of running the in-house method is only 50% of that for ViroSeq method (112$ vs 300$), thus making it cost effective. CONCLUSIONS: The validated cost effective in-house method may be used to collect surveillance data on the emergence and transmission of HIV-1 drug resistance in resource limited countries. Moreover, the wide applications of a cost effective and validated in-house method for HIV-1 drug resistance testing will facilitate the decision making for the appropriate management of HIV infected patients.